Diplomatic Amateurs or Qualified Professionals? Profiling the American Ambassador - Calin, Costel; Fitzpatrick, Kathy R. (White House Studies, 2013)
Are U.S. ambassadors qualified to lead America’s diplomatic missions abroad? This age-old question—often raised but seldom seriously considered by diplomacy scholars— is the focus of this study, which examined the professional credentials of American ambassadors appointed by former U.S. President George W. Bush. The article explores the relationship between the professional status of U.S. ambassadors and the power status and economic importance of host countries. The results showed that preferred destinations for amateur ambassadors were mostly Western European countries and countries with which the United States has large economic exchanges. Professional ambassadors were mostly appointed to African and Asian countries and to countries that have lower trade with the United States. The vast majority of semiprofessional diplomats were appointed to the most powerful countries.
Keywords: AMERICAN ambassadors; BUSH, George W. (George Walker), 1946-; DIPLOMATIC & consular service; GOVERNMENT missions; INTERNATIONAL relations; PRESIDENTS of the United States; dept.psc

A Post-Racial Change Is Gonna Come: Newark, Cory Booker, and the Transformation of Urban America - Wharton, Jonathan L. (Palgrave Macmillan, 2013)
Keywords: Booker, Cory; Metropolitan government; Case studies; Case studies; Mayors; Case studies; Newark (N.J.); Case studies; Post-racialism; Election; African American mayors; New Jersey; Newark; Newark; Urbanization; Political aspects; Politics and government; Newark (N.J.); Race relations; United States; dept.psc; faculty_collection

A Post-Racial Change Is Gonna Come: Newark, Cory Booker, and the Transformation of Urban America - Wharton, J. (Springer, 2013)
This work offers a political and historical analysis of Newark's modern politics since 1950, culminating with Mayor Cory Booker's rise to power and prominence both in the city and in American political consciousness. Newark's recent political history offers an interesting case study in mayoral elections, community development, and coalition building politics. While Newark is the quintessential post-industrial city, Booker has received critical attention for his post-racial politics since he frequently bypasses racial and traditional urban politics. At the same time, relations between the mayor, the municipal council, and Newark's diverse communities were often so fractious that sustainable coalition building proved to be an elusive goal to resolve longstanding crime, education, and other social problems. Based on original interviews with Cory Booker, city council members, and other prominent Newark politicians, A Post Racial Change is Gonna Come is a powerful history of how Newark became the focal point for transformative politics in urban America.
Keywords: Political Science / General; Political Science / History & Theory; Political Science / Political Economy; Political Science / Public Affairs & Administration; Political Science / Public Policy / City Planning & Urban Development; Political Science / Public Policy / General; Political Science / World / European; Science / Earth Sciences / Geography; Social Science / Ethnic Studies / General; dept.psc

The United States and Greece in the twentieth century - Iatrides, J.O. (Greece in the Twentieth Century, 2013)
Keywords: dept.psc